Herbs for horses - Fors, Maria (2010)
The aim of this study was to find out how many and which of the herbs used for horses that have been scientifically studied with results to justify the use. In order to find out which herbs that are commonly used by horse-owners a phone interview was performed where six companies selling herbs for horses was contacted and asked to provide information on the most sold herbs for horses in Sweden. Devil's claw (Harpagophytum procumbens), chamomile (Matricaria recutita), dandelion (Taraxacum officinalis), nettle (Urtica dioica) and monk's pepper (Vitex agnus-castus) where the most sold herbs, followed by marshmallow (Althaea officinalis), burdock (Arctium lappa), marigold (Calendula officinalis), purple coneflower (Echinacea angustifolia/purpurea), cleavers (Galium aparine), licorice (Glycyrrhiza glabra), rose hip (Rosa canina), thyme (Thymus vulgaris) and vervain (Verbena officinalis), in no particular order. Of the most used herbs, research with focus on the use for horses was found for purple coneflower, licorice, devil's claw, monk's pepper, rose hip, thyme, and vervain. These studies did not cover the whole range of traditional use for the mentioned herbs, and more studies are needed to be able to claim that these herbs have, or have not, scientific support for use in equine management.